F-response behaviour in a control population. Issue 11 (November 1985) - Peioglou-Harmoussi, S; Howel, D; Fawcett, P R; Barwick, D D
Abstract : Various parameters of the F-response including minimal and maximal latency, chronodispersion, amplitude (absolute and F%M) and duration have been determined for a sample of 20 responses in the median and ulnar nerves bilaterally in normal healthy subjects of both sexes aged between 12 to 81 years. Side to side comparisons revealed no significant differences in any of the parameters except for slightly longer minimum F latencies in the right median nerve. Strong correlations were found between minimal and maximal F latencies and height, while much weaker relationships were found between these parameters and age. There was a slight but significant relationship between F%M and age, but no age or sex related changes were noted for any of the remaining F-response parameters.